The Current Status of Medical Parasitology in Iran: Developing a Roadmap, Structural Mapping, and Proposed Scenarios for the Future of this Field - Seyed Mahmoud Sadjjadi; Mehdi Mohebali; Iraj Sharifi; Abdolhossein Dalimi Asl; Ali Haghighi; Abdollah Rafiei; Mostafa Rezaeian; Gholamhossein Edrissian; Hossein Keshavarz Valian; Mohammad Bagher Rokni; Mohammad Fallah; Hossein Yousefi Darani; et al. (Iranian Journal of Parasitology, 2025)
Background: We aimed to review and analyze the status of Medical Parasitology course including current problems and challenges on human resources, infrastructure, research capacities, educational and investigative priorities in Iran, and to develop a roadmap and future development in this field.